Real‐world use of emicizumab in Chinese children with hemophilia A: Retrospective data from a comprehensive care center - Qianqian Mao; Zhenping Chen; Guoqing Liu; Gang Li; Yingzi Zhen; Xiaoling Cheng; Zekun Li; Wanru Yao; Di Ai; Zhengping Li; Nan Wang; Man‐Chiu Poon; et al. (Pediatric Investigation)
ABSTRACT Importance Emicizumab (EMI) is efficacious and safe for hemophilia A (HA) prophylaxis. However, its high cost poses a challenge in China. Objective To explore the possibility of using reduced‐dosage EMI in Chinese HA children. Methods We conducted a retrospective study for HA children in our Comprehensive Care Center. Data were collected pre‐ and post‐EMI treatment to evaluate bleeding rates. Laboratory analyses included factor VIII (FVIII)‐like activity and EMI concentration measurements. Results Thirty‐four HA children receiving EMI prophylaxis for a median (range) 24.5 (2.5–47.9) months by June 2023. Of these, 25 (73.5%) were under 3 years of age, 26 (76.5%) had severe hemophilia and 12 (35.3%) were minimally treated or previously untreated patients. Thirty‐one (91.2%) of the 34 patients received reduced‐dosage EMI for economic reasons. EMI concentration and FVIII‐like activity measured showed a strong correlation. Overall, while on EMI, their annual treated bleeding rate (ATBR) and annual bleeding rate (ABR) decreased significantly (2–0) while their zero‐bleeding rate (ZBR) increased significantly (11.5%–65.4%). After 6 months of EMI, there was no significant difference in ATBR and ABR among various maintenance dosages. However, ZBR was significantly lower in dosages under 4 mg/kg (P = 0.0156). Receiver operator characteristic curves suggested the following cutoff values for zero bleeding: EMI 4‐weekly maintenance dosage 3.8 mg/kg, EMI concentration 48.1 μg/mL, and FVIII‐like activity 15.4 IU/dL. Interpretation We showed EMI effectively prevented bleeding even at reduced dosages. However, the bleeding risk may be higher with EMI 4‐weekly maintenance dosage <3.8 mg/kg, EMI concentration <48.1 μg/mL, and FVIII‐like activity <15.4 IU/dL for zero bleeding. It is important that dosage reduction be done rationally. Dosage tailoring is possible.